Urban resilience and crisis management: Perspectives from France and Germany. - Weichselgartner, Juergen; Guézo, Bernard; Beerlage, Irmtraud; Després, Christian; Fekete, Alexander; Hufschmidt, Gabriele; Lussignoli, Orsola; Mey-Richters, Stefanie; Naumann, Jens; Wienand, Ina (Springer, 2018)
The resilience concept and its application in the context of urban security encounter a series of grounded challenges for scientists, policy-makers, planning bodies, and the manifold authorities of jurisdiction and civil services. This chapter outlines a joint effort to explore structural and functional similarities and differences in France and Germany with regard to crisis management in urban systems, with the ultimate goal of identifying potential pathways of applying the resilience concept and exploring the potential for cross-national collaborative actions. Specific aspects of urban resilience and crisis management are portrayed: cross-border and international aspects, community resilience, psychosocial crisis management, and knowledge and information. In both countries, past and ongoing activities demonstrate the potential of connecting scientists and decision-makers in policy and practice to integrate multiple perspectives, bridging existing barriers between research, policy, and operational practice, and stimulating new technologies and innovative solutions. Furthermore, it became clear that enhancing urban resilience requires governance structures that promote cooperation among and between science, policy, and practice. Likewise, crisis management practices can be enriched through bi-national partnerships, collective activities, and shared co-management efforts. It is therefore suggested to further examine the various network strategies within hierarchical and horizontal collaboration structures and address the question of how the structural arrangements for collaboration within crisis management networks influence disaster resilience in urban areas.
Keywords: Stadt; Kommunalverwaltung; Krisenmanagement; Katastrophenschutz; Resilienz; Verwaltungshandeln; Kommunale Zusammenarbeit; Städtevergleich; Internationaler Vergleich